Pengaruh Strategi Pemasaran dan Bauran Pemasaran Terhadap Keputusan Pelanggan Membeli Produk Alat Kesehatan di PT. Multy Synergy Persada dengan Citra Perusahaan sebagai Intervening - R. Deni Fajar Fitriansyah; Hermawan Hermawan; Christina Ekawati (Syntax Idea)
This research aims to analyze the influence of Promotion (X1), Price (X2), Place (X3), Product (X4), Segmentation (X5), Targeting (X6), Positioning (X7) on the purchase decisions (Z) of Medical devices at PT. Multy Synergy Persada, with Company Image (Y) as an Intervening Variable. The background of this study reflects the importance of understanding how marketing factors such as promotion, price, distribution, product, market segmentation, targeting, and positioning can affect consumer purchase decisions in the Medical devices industry. PT. Multy Synergy Persada faces intense competition in the Medical devices market, making it crucial to comprehend the factors influencing customer purchase decisions and the role of the company image as an intervening variable in designing effective marketing strategies. The study's population comprises PT. Multy Synergy Persada's customers, with a target of 100 respondents, were selected through purposive sampling. The analysis method employed is path analysis using the SmartPLS application. The research results indicate that the validity and reliability tests meet the established standards. Furthermore, the hypothesis tests' outcomes demonstrate that all hypotheses related to the variables Promotion (X1), Price (X2), Place (X3), Product (X4), Segmentation (X5), Targeting (X6), Positioning (X7) regarding purchase decisions (Z) are accepted. The same applies to the variables Promotion (X1), Price (X2), Place (X3), Product (X4), Segmentation (X5), Targeting (X6), Positioning (X7) concerning Company Image (Y). These findings also suggest that the company image mediates the relationship between all independent variables and purchase decisions. In conclusion, this research indicates the pivotal role of marketing strategies and marketing mix for PT. Multy Synergy Persada in enhancing the company image and influencing customer purchase decisions related to Medical devices products.